2023
DOI: 10.3390/jcm12226971
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic Bowel Dysfunction in Patients with Spinal Cord Injury and Multiple Sclerosis—An Updated and Simplified Treatment Algorithm

Fredrika Magnuson,
Peter Christensen,
Andrei Krassioukov
et al.

Abstract: Neurogenic bowel dysfunction (NBD) is a common condition in individuals with spinal cord injury (SCI) or multiple sclerosis (MS). It usually entails constipation, difficult evacuation of the rectum, and fecal incontinence (FI); often in combination. It is highly burdensome for affected patients and is correlated with poor quality of life. The current treatment algorithm, or treatment pyramid, does not completely correspond to actual clinical practice, and the known and classical pyramid contains both treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…TAI is a second-line intervention for patients with NBD and is often recommended after patients experience insufficient results with standard or conservative care [ 12 , 14 , 15 , 20 ]. This review article focuses on the system with a rectal catheter with a balloon.…”
Section: The Role Of Tai In Managing Nbdmentioning
confidence: 99%
See 4 more Smart Citations
“…TAI is a second-line intervention for patients with NBD and is often recommended after patients experience insufficient results with standard or conservative care [ 12 , 14 , 15 , 20 ]. This review article focuses on the system with a rectal catheter with a balloon.…”
Section: The Role Of Tai In Managing Nbdmentioning
confidence: 99%
“…With the participation of several multi-disciplinary experts, bowel physiology was identified as a top priority to elucidate the effects and interventions on bowel function. Since this meeting, the Consortium of Spinal Cord Medicine Clinical Practice Guidelines on the Management of Neurogenic Bowel Dysfunction in Adults after SCI have been updated and several consensus statements have been developed inclusive of patients’ input [ 11 , 12 , 13 , 14 , 15 ]. More recently, Dietz et al identified that meticulous attention to the patient is required during the first five years postinjury to achieve a successful bowel management plan that is sustained for 25 years [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations